Anaplastic Carcinoma of the Pancreas Mimicking Submucosal Gastric Tumor: A Case Report of a Rare Tumor. (8th December 2013) - Fujiogi, Michimasa; Kobayashi, Takashi; Yasuno, Masamichi; Tanaka, Michio
Abstract : Anaplastic carcinoma of the pancreas (ACP) is a rare neoplasm of the pancreas. ACPs are aggressive neoplasms with a poorer prognosis than poorly differentiated ductal adenocarcinomas of the pancreas. The 3-year survival rate of patients with ACP is less than 3%, with a life expectancy of 10 to 20 months. We describe here a 64-year-old man with ACP mimicking a submucosal gastric tumor. The patient was found to have a giant mass mimicking a submucosal tumor. Total gastrectomy with splenectomy and partial resection of the tail of the pancreas were performed. The pathological diagnosis was ACP, with immunohistological findings showing pleomorphic-type ACP. Because the surgery was noncurative, the patient received adjuvant chemotherapy with paclitaxel but died of peritoneal dissemination and multiple liver metastases 4 months after surgery.